Patients’ satisfaction regarding facilities and services provided at AYUSH clinics of primary health centres in rural Puducherry - Boovaragasamy, Chithra; Narayanan, Seetharaman (International Journal Of Community Medicine And Public Health, 2019)
Background: Patient satisfaction is a crucial component of the health care system in today’s competitive modern era. There is a limited literature describing the patient satisfaction on AYUSH care and therefore this study was undertaken to assess the satisfaction about facilities, healthcare providers and treatment among the patients attending selected AYUSH-attached PHCs in rural Puducherry. Methods: A facility based cross-sectional study was conducted among the patients who attended AYUSH clinics at 4 selected PHCs of Puducherry over a period of one year. Personal Interviews using semi-structured pretested proforma was conducted for capturing information on socio-demographic variables, satisfaction regarding the facilities and health care providers. Telephonic interviews were conducted two weeks after the centre-based personal interviews, to assess the patients’ treatment satisfaction levels. Results: Out of the 584 patients interviewed, 71.23% rated as very good/excellent their interaction with the healthcare providers, with regards to satisfaction about the infrastructure facilities, the proportion rating very good/excellent ranged from 64.47% to 93.93% across the different AYUSH PHCs. Conclusions: Overall satisfaction about the quality of services and treatment was good among the patients.